The cardiac complications of COVID-19: many publications, multiple uncertainties. (11th November 2020) - Al-Mohammad, Abdallah; Partridge, David G; Fent, Graham; Watson, Oliver; Lewis, Nigel T; Storey, Robert F; Makris, Michael; Chico, Timothy J
Abstract : Abstract: Since the first description of COVID-19 in December 2019, more than 63, 000 publications have described its virology, clinical course, management, treatment and prevention. Most physicians are now encountering, or will soon encounter, patients with COVID-19 and must attempt to simultaneously assimilate this avalanche of information while managing an entirely novel disease with few guiding precedents. It is increasingly clear that, although primarily a respiratory illness, COVID-19 is associated with cardiovascular complications. However, the true incidence of direct cardiac complications remains unclear, as all complications thus far reported can also occur in patients without COVID-19. In this review, we briefly summarise and critically appraise the data on cardiac complications associated with COVID-19 and describe some cases from our own experience. We identify unresolved questions and highlight the many uncertainties in this developing field.